CAN ECO-ENGINEERING MINDS BE ENHANCED? A STUDY OF MALAYSIAN POLYTECHNIC STUDENTS IN GREEN ENTREPRENEURSHIP EDUCATION - Norsalwati Mohd Razalli; Irdayanti Mat Nashir; Mazura Mansor; Zainal Ariffin Ahmad (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The imperative for sustainable development has heightened focus on eco-engineering and green entrepreneurship. It investigates the role of the KAP Model in shaping students’ eco-consciousness and entrepreneurial mindset. While environmental awareness is rising, there continues to be a dearth of developing effective eco-engineering minds, especially in entrepreneurship. As such, this study examines whether Malaysian Polytechnic students’ eco-engineering mindset can be enhanced through targeted green entrepreneurship education. This paper addresses this gap by examining how cognitive, affective, and behavioural factors nurture sustainable attitudes of Polytechnic students. This quantitative research method used an online questionnaire to 155 students from 12 Polytechnics in Peninsular Malaysia. The data analysis conducted includes descriptive and inferential statistics for data using Statistical Package for Social Science (SPSS) Version 26. The data from a diverse sample of Polytechnic students in entrepreneurship courses allowed us to provide real-world insights into the impact of education on nurturing eco-engineering minds. The results revealed that the Knowledge, Attitudes, and Practices (KAP) Model was not significantly different in gender and Cumulative Grade Point Average (CGPA) scores of students on the KAP of green entrepreneurship. The study highlighted the opportunity for targeted pedagogical interventions to nurture eco-entrepreneurs among Malaysian and global students.